MSIAC – Supporting the Munitions Safety Community - Ernest L. BAKER (Problemy Mechatroniki, 2016)
The NATO Munitions Safety Information Analysis Center (MSIAC) is a multinational collaboration that collects, stores, and analyses technical information related to Munitions Safety (MS) and Insensitive Munitions (IM). This paper and presentation will provide an overview of MSIAC’s recent achievements in advancing munition safety efforts on behalf of its member nations. MSIAC supports its member nations through a variety of products and services. Poland is anticipated to become a member nation near the end of 2016. In addition to a core responsibility of addressing technical questions related to Munitions Safety posed by nations, MSIAC has a diverse programme of work aimed at developing and sharing the related underpinning scientific knowledge. This is then applied to support policy implementation and development related to munition safety. Some examples of current activities are given in this paper as well as future activities.